Driving Sustainable Energy Transitions through Business Intelligence: How Green Innovation Orientation Shapes ESG Outcomes - Tarawneh, Abeer; Alzghoul, Amro (International Journal of Energy Economics and Policy, 2025)
The transition to sustainable energy systems is contingent upon firms’ capacity to transform data into actionable improvements in both operational efficiency and environmental performance. This study investigates the role of business intelligence, conceptualized as a socio-technical capability for integrating and analyzing operational and environmental data, in enhancing ESG outcomes within energy enterprises. It further examines whether a green innovation orientation strengthens this relationship, particularly within the context of an emerging economy. The empirical analysis focuses on the energy sector in Jordan and employs a quantitative, cross-sectional survey design. A total of 250 survey invitations were distributed to managers and technical professionals across organizations engaged in generation, transmission, distribution, and energy services, yielding 183 valid responses. All constructs were modeled reflectively and analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that business intelligence is positively associated with ESG outcomes, operationalized through measures of energy efficiency, environmental performance, and sustainability practices. Moreover, the findings demonstrate that green innovation orientation exerts a positive moderating effect, amplifying the relationship between business intelligence and ESG outcomes. Theoretically, the results integrate resource-based and dynamic-capabilities views with sustainability-transitions scholarship by specifying an orientation–capability complementarity: business intelligence is necessary but insufficient for sustainability gains unless coupled with a strong green innovation orientation. Practically, managers should prioritize ESG-relevant analytics (loss localization, asset-health forecasting, and emissions-intensity optimization), institutionalize green innovation orientation in executive KPIs and investment gates, and strengthen data governance. The study offers sector-specific evidence from Jordan and outlines a scalable framework for leveraging BI to accelerate decarburization and governance outcomes in energy systems.